Identification of Machine Damage Causes Production Failure Using the Method Failure Modes and Effects Analysis At the North Distribution Pump House PT XYZ - Muhammad Irfan; Gatot Basuki H.M. (Prosiding SENASTITAN: Seminar Nasional Teknologi Industri Berkelanjutan, 2023)
The human need for clean water is very high to meet the needs of life, water also plays a role in other functions such as irrigation of agricultural land, and industry is also very dependent on water needs. It is clear that all activities in this world cannot be separated from the need for water. Sometimes the water supply fails in the production process. unit volume. XYZ is a company that provides clean water to the local community, which is also a government service to the community. Process failure risk analysis is one of the companies that can identify all the risks that affect process failure, especially the production process, which ultimately affects system failure. Determination of the failure risk of the north distribution pump using the failure and effect analysis (FMEA) method. This method is included in the risk management method for identifying potential errors in the production process, which can be used to determine corrective actions to overcome or reduce errors in the production process. Each root cause of failure is considered in terms of severity, frequency (how often the failure occurs), and detection (how quickly the failure is detected). Multiples of three are called the Risk Priority Number (RPN). Priority is determined based on the highest RPN value of possible system failure and warm shutdown (160). It is recommended that repairs should be routinely carried out three times a week taking into account the condition of each part to minimize damage.